Effect of Sowing Date of Sweet Corn on Potato + Sweet Corn Intercropping System (Bangladesh Agronomy Journal, 2016)
An experiment was conducted at the Agronomy research field of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur and at Regional Agricultural Research Station, Burirhat, Rangpur during Rabi season of 2013-14 and 2014-15 to find out optimum sowing date of sweet corn in potato + sweet corn intercropping system for getting maximum yield and economic return. Six treatments viz., simultaneous sowing of potato and sweet corn, sweet corn sown at 10 days after potato planting (DAPP), sweet corn sown 20 DAPP, sweet corn sown 30 DAPP, sole potato and sole sweet corn were tested in this study. Sweet corn sown at 20 DPP produced the highest potato equivalent yield (Joydebpur: 41.41 t ha-1 in 2013-14 and 42.22 t ha-1 in 2014-15 and Rangpur: 42.29 t ha-1 in 2013-14 and 42.52 t ha-1 in 2014-15). The highest gross return at Joydebpur Tk. 431050 ha-1 and at Rangpur Tk. 436248 ha-1, gross margin at Joydebpur Tk. 286805 ha-1 and at Rangpur Tk. 271985 ha-1 and benefit cost ratio at Joydebpur 2.99 and at Rangpur 3.01 were observed over the years in the same treatment. In this treatment, tuber yield was reduced 3.4-4.1% in Joydebpur and 7.8-8.4% in Rangpur due to intercropping. The result indicated that sweet corn sown 20 DAPP might be suitable intercrop combination for getting maximum yield and economic return.Bangladesh Agron. J. 2015, 18(2): 15-21